ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU WANITA USIA SUBUR (WUS) TERHADAP ASUHAN CONTINUITY OF CARE (COC) - Rafika Oktova; Yulizawati Yulizawati; Henni Fitria (STIKes Al-Insyirah Pekanbaru, 2023)
The increase in maternal and infant mortality in Indonesia requires major efforts to reduce this number. One of the efforts made is to carry out continuous care midwifery (continuity of care). It is necessary to inform all Women of Reproductive Age (WRA) regarding continuity of care midwifery care in order to reduce complications and morbidity in mothers. However, access to midwifery services cannot be carried out regularly and continuously due to various factors. The purpose of this study was to determine the factors that influence the behavior of women of childbearing age (WRA) towards continuity of care in Nagari Pagaruyung, Tanjung Emas District, Tanah Datar Regency. This research is a quantitative study with a cross sectional design. The study population was all WRA, totaling 1,801 people. A sample of 95 people was taken using a purposive sampling technique that met the inclusion and exclusion criteria. The research instrument is a questionnaire. Data analysis with chi-square test (α<0.05). Statistical test results for age (p=0.763), education (p=0.110), occupation (p=0.008), knowledge (p=0.019), and attitude (p=0.000). There is a relationship between work factors, knowledge, and attitudes with the behavior of women of childbearing age towards continuity of care midwifery care. There is no relationship between age and education with the behavior of Women of Reproductive Age (WRA) towards midwifery continuity of care. It is hoped that health workers can provide continuity of care midwifery care to Women of Reproductive Age (WRA).